Translation and the Authorial Image: the Case of Federico García Lorca’s Romancero gitano - Linn, Stella (TTR, 2003)
AbstractDespite Barthes’s claim that the author is dead, leaving the scene for his work, freed from its all too personal origin, I would like to argue that the author image is far from absent in the practice of literary translation. On the one hand, the author’s image within a particular literary and social system may determine which work is translated, and even how it is translated. On the other hand, it seems likely that some characteristics of a persona will be highlighted more than others, depending on which source texts are selected for translation and on how the author and his or her works are presented in prefaces and commentaries accompanying the translations. Moreover, the translation strategy may enhance the prevailing tendencies within reception and thus contribute to a certain perception of the author in the target culture. In this paper I will investigate these hypothetical connections, taking as an example the Spanish author Federico García Lorca and a number of translations of his Romancero gitano (1928) into French, English, and Dutch. I will examine a possible correlation between the prevailing “folkloristic” image of Lorca in the early literary criticism, and the emphasis on romantic, naïve and mythological aspects in translations of his work, and conversely, the later, more complex and gloomy image presented of the author, and translation strategies which highlight elements that correspond to that view.